2016
DOI: 10.1253/circj.cj-16-0011
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Acetone Concentration Is Related to Hemodynamic Severity in Patients With Non-Ischemic Chronic Heart Failure

Abstract: Background:We hypothesized that exhaled acetone concentration (EAC), reflecting altered blood ketone body metabolism and increased acetone exhaust because of pulmonary congestion in heart failure (HF), would correlate with hemodynamic parameters in patients with non-ischemic chronic HF. Methods and Results:We prospectively enrolled 102 non-ischemic HF patients with New York Heart Association (NYHA) class I-III. Exhaled breath was collected after an overnight fast. Echocardiography and cardiac catheterization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
2
35
1
Order By: Relevance
“…Previous studies showed single exhaled acetone measurement could be diagnostic tool and could evaluate heart failure severity. [3][4][5][6] In contrast, in this preliminary study, we found out decreased exhaled acetone concentration in the improved clinical course of heart failure. Decreased exhaled acetone concentration might suggest improvement of heart failure severity and serial exhaled acetone measurements could monitor effects of treatment for heart failure.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous studies showed single exhaled acetone measurement could be diagnostic tool and could evaluate heart failure severity. [3][4][5][6] In contrast, in this preliminary study, we found out decreased exhaled acetone concentration in the improved clinical course of heart failure. Decreased exhaled acetone concentration might suggest improvement of heart failure severity and serial exhaled acetone measurements could monitor effects of treatment for heart failure.…”
Section: Discussioncontrasting
confidence: 67%
“…Exhaled acetone concentration is one of the expected compounds to be a breath biomarker in patients with heart failure. [3][4][5][6] Exhaled acetone concentration is known to be correlated with New York Heart Association (NYHA) class and brain natriuretic peptide in patients with heart failure. 3) Moreover, exhaled acetone concentration could have prognostic impact in patients with heart failure.…”
mentioning
confidence: 99%
“…11 Our group, in a previous study, showed that not only HF patients (n = 89) have higher breath acetone concentration when compared with healthy people but also that acetone levels increase according to NYHA class, which suggests an association between acetone levels and the severity of the disease. 4 A group of researchers from the Cleveland Clinic also observed higher levels of breath acetone in 35 patients with ADHF when compared with healthy 13 Considering all these findings, it is possible to say that the role of acetone as a biomarker of ADHF is well established. However, this is the first time EBA is unveiled as a biomarker of chronic HF, even considering patients with different comorbidities.…”
Section: Discussionmentioning
confidence: 96%
“…8) Previous studies on exhaled acetone concentration in heart failure excluded patients with diabetes mellitus, and there have been no reports about exhaled acetone concentration in heart failure with diabetes mellitus. 2,3) Diabetes is the most common cause of elevated blood ketones. Especially in diabetic ketoacidosis, elevated blood ketone bodies are produced under low insulin and high counterregulatory hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…1) Acetone, a volatile ketone body component, is increased in the breath of heart failure patients in relation to heart failure severity. 2,3) Diabetes mellitus is the representative disease associated with ketogenesis, 4) and is also known to affect exhaled acetone concentration. 5) However, there have been no reports of exhaled acetone concentration in diabetic patients with heart failure.…”
mentioning
confidence: 99%